2021
DOI: 10.1002/mas.21716
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry‐based methods for the advanced characterization and structural analysis of lignin: A review

Abstract: Lignin is currently one of the most promising biologically derived resources, due to its abundance and application in biofuels, materials and conversion to value aromatic chemicals. The need to better characterize and understand this complex biopolymer has led to the development of many different analytical approaches, several of which involve mass spectrometry and subsequent data analysis. This review surveys the most important analytical methods for lignin involving mass spectrometry, first looking at method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 179 publications
(287 reference statements)
1
46
0
Order By: Relevance
“…LDI-MS experiments indicated that the presence of specific peaks, the way in which the peaks were grouped, and the global shape of the spectrum reflected the global structure of lignin oligomers [73]. LDI-MS analysis revealed a wide mass distribution of lignin oligomers [74,75]. However, the experimental conditions allowed the analysis of monocharged species with low fragmentation.…”
Section: Methodsmentioning
confidence: 99%
“…LDI-MS experiments indicated that the presence of specific peaks, the way in which the peaks were grouped, and the global shape of the spectrum reflected the global structure of lignin oligomers [73]. LDI-MS analysis revealed a wide mass distribution of lignin oligomers [74,75]. However, the experimental conditions allowed the analysis of monocharged species with low fragmentation.…”
Section: Methodsmentioning
confidence: 99%
“…Lignin has great potential as a feedstock for the sustainable generation of high-value aromatic compounds that can substitute for the excess use of crude oil [ 163 ] therefore, it is essential to understand lignin structures so that proper degradation methods can be applied accordingly to produce high-value small molecules. Lignin comprises a group of structurally complex chemicals that are constructed from three different monomeric units (G, S and H) [ 164 ]. These lignin monomers are connected with each other via many different linkage patterns, thus ensuring that the structural elucidation of lignin is not an easy task.…”
Section: Applications Of Mass Spectrometry-based Techniques For Struc...mentioning
confidence: 99%
“…FT-ICR MS methodologies play an integral part in the analysis and understanding of the complex lignin molecules. 14…”
Section: Introductionmentioning
confidence: 99%
“…FT-ICR MS methodologies play an integral part in the analysis and understanding of the complex lignin molecules. 14 Here we report an HPA-CTH reaction system for KL valorization under mild conditions without external H 2 , which is a sustainable biorefinery strategy. The KL would be almost converted to liquid oils and phenolic monomers with high yields in isopropanol using SiW 12 .…”
Section: Introductionmentioning
confidence: 99%